The Influence of Work Ability, Job Training, and Teamwork on Employee Performance at PT. Semen Tonasa, Pangkep Regency - Elsa Fitri Nurhidayah; Muhammad Rusydi; M. Yusuf Alfian Rendra Anggoro (Green Publisher Indonesia, 2024)
This research aims to determine and analyze the influence of work ability on employee performance, job training on employee performance, and teamwork on employee performance at PT. Semen Tonasa Pangkep Regency. The data collection technique used in the research is related to surveys by distributing questionnaires and documentation studies. The sample used in this research was 110 respondents. The data analysis method used is multiple linear regression analysis which is processed with the help of SPSS 24 software. The results of this research show that work ability has a positive and significant effect on employee performance, job training has a positive and significant effect on employee performance, teamwork has a positive and significant effect on employee performance at PT. Semen Tonasa Pangkep Regency.